Self-Efficacy of Undergraduate Human Services Students With Integrated Behavioral Health - Kristy Carlisle; Nic Schmoyer; Danielle Rodgers; Katherina Nako; Richie Kubilus; Zubede Akpakir (Journal of Human Services)
Human services professionals (HSPs) are poised to contribute to interprofessional collaboration (IPC) in Integrated Behavioral Health (IBH) settings as care enhancers. Interprofessional Education (IPE) effective for training HSPs requires changes or addition to curriculum. The purpose of the current study was to present workshops adjunct to curriculum to HSPs targeting their engagement in IBH settings. The study explored their self-efficacy with IPC after such training using a pre- and post-test design. Results indicated a statistically significant increase in self-efficacy from before and after the workshop. Discussion includes implications for human services educators in using workshops to augment the IPE their students undergo.